Static and fatigue behavior of shear stud connection embedded in UHPC. (December 2021) - Huang, Yang; Chen, Shiming; Gu, Ping
Abstract: In the UHPC-steel composite bridge deck, the thickness of UHPC layer is usually only 40–50 mm, so short headed studs are used for shear connection of the interface between UHPC and steel deck. In this paper, the refined finite element (FE) model of push-out specimen is established to explore failure mode of the stud connection, damage concentration location of UHPC and load-slip behavior of UHPC-steel interface. Verified against the existing test results, FE parameter analysis is conducted, and shear strength formula and load-slip relationship of short headed stud embedded in UHPC are proposed. With the consideration of reduction effect of group studs, the shear strength formula of single stud can be used to simplify the calculation safely. A nominal shear stress S-N curve with 95% survival probability is proposed, fitted by the International Institute of Welding (IIW) recommended method. Based on the fracture mechanics method, a fatigue life evaluation formula of stud under influence of multiple factors is established. By the comparative analysis between the proposed formulas and the existing codified formulas for stud connection in ordinary concrete, the recommended formula for the fatigue strength of stud in UHPC is proposed.